Polymorphic loci analysis of 16s ribosomal RNA gene of economically important marine lizardfish Bombay duck (Harpadon nehereus) (Bangladesh Journal of Zoology, 2019)
Attempts were made to combine morphological and molecular techniques for identification and analysis of evolutionary relationship of commercially important marine lizardfish (Bombay duck) from the Bay of Bengal. For molecular identification, mitochondrial DNA (mtDNA) was extracted using CTAB extraction protocol and 16S rRNA gene was amplified by PCR method. Morphological identification was supported by molecular data generated by 99% identity of BLAST search result of Harpadon nehereus. The nucleotide sequence of H. nehereus was 586 bp long and the G+C content was 51% and intraspecies polymorphic sites were 0.5%. According to interspecies polymorphic sites analysis, 4.9% polymorphism was observed when H. nehereus and H. microchir were compared. Phylogenetic tree was constructed and both the Harpadon spp. formed a monophyletic clade. This analysis will be used to study molecular diversity as well as conservation of this fish species.Bangladesh J. Zool. 47(1): 49-57, 2019